Clustered protocadherins methylation alterations in cancer - Vega-Benedetti, Ana Florencia (Clin Epigenetics, 2019)
BACKGROUND: Clustered protocadherins (PCDHs) map in tandem at human chromosome 5q31 and comprise three multi-genes clusters: α-, β- and γ-PCDH. The expression of this cluster consists of a complex mechanism involving DNA hub formation through DNA-CCTC binding factor (CTCF) interaction. Methylation alterations can affect this interaction, leading to transcriptional dysregulation. In cancer, clustered PCDHs undergo a mechanism of long-range epigenetic silencing by hypermethylation. RESULTS: In this study, we detected frequent methylation alterations at CpG islands associated to these clustered PCDHs in all the solid tumours analysed (colorectal, gastric and biliary tract cancers, pilocytic astrocytoma), but not hematologic neoplasms such as chronic lymphocytic leukemia. Importantly, several altered CpG islands were associated with CTCF binding sites. Interestingly, our analysis revealed a hypomethylation event in pilocytic astrocytoma, suggesting that in neuronal tissue, where PCDHs are highly expressed, these genes become hypomethylated in this type of cancer. On the other hand, in tissues where PCDHs are lowly expressed, these CpG islands are targeted by DNA methylation. In fact, PCDH-associated CpG islands resulted hypermethylated in gastrointestinal tumours. CONCLUSIONS: Our study highlighted a strong alteration of the clustered PCDHs methylation pattern in the analysed solid cancers and suggested these methylation aberrations in the CpG islands associated with PCDH genes as powerful diagnostic biomarkers. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13148-019-0695-0) contains supplementary material, which is available to authorized users.